Untangling the spatial patterns of evolution of specialized villages and influencing factors - Niu, Ning; Wang, Chao; Jin, He (Frontiers in Ecology and Evolution, 2023)
The development of specialized villages (SVs) is of great importance for rural revitalization. However, few studies have paid attention to the development of SVs. To fill the research gaps, this study integrated SVs, terrain, resource, traffic, market, and economy data to characterize the development of SVs from 2017 to 2021 and explore its influence factors by the Random Forest Regression model in Henan, China. The results depicted: (1) the sustainably developed SVs were mainly distributed in the plain and the transition zone of mountain-hilly, mountain-plain, and hilly-plain, showing a spatially aggregated polycentric characteristic; (2) the market is the key factor for the development of SVs in the transition zone of mountain-hill or mountain-plain, and the traffic factor mainly influences SVs in the plain and the transition zone of hill-plain; (3) compared to the factors influencing the formation of SVs, the influence of terrain and traffic factors on the development of SVs was decreasing, and the influence of market and economic factors was showing an increasing trend. The results of this study can provide practical strategies for the development of SVs in the under-developed areas of interior.